2016
DOI: 10.1007/s00264-016-3151-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of posterior ligamentous complex injury in thoracolumbar fractures using non-MRI imaging techniques

Abstract: On plain radiographs the presence of LK greater than 20 °(CI 64-95) and ISD difference greater than 2 mm (CI 70-97) can predict PLC injury. These guidelines may be utilised in the emergency room especially when the associated cost, availability and time delay in performing MRI are a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Hiyama et al 24 assessed loss of vertebral body height, local kyphosis, vertebral body translation, canal compromise, interlaminar distance, supraspinous distance, and interspinous distance in 40 patients with TL fractures and concluded that a local kyphosis >20° and increased supraspinous distance were associated with PLC injury. Rajasekaran et al 25 analyzed 60 patients with possible PLC injury using STIR MRI sequences as a gold standard to identify PLC injury. The authors reported that local kyphosis of >20° and interspinous distance increase of ≥2 mm compared with adjacent levels may serve as a radiological criterion to predict PLC injury, especially in the scenario of emergency trauma where MRI is not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hiyama et al 24 assessed loss of vertebral body height, local kyphosis, vertebral body translation, canal compromise, interlaminar distance, supraspinous distance, and interspinous distance in 40 patients with TL fractures and concluded that a local kyphosis >20° and increased supraspinous distance were associated with PLC injury. Rajasekaran et al 25 analyzed 60 patients with possible PLC injury using STIR MRI sequences as a gold standard to identify PLC injury. The authors reported that local kyphosis of >20° and interspinous distance increase of ≥2 mm compared with adjacent levels may serve as a radiological criterion to predict PLC injury, especially in the scenario of emergency trauma where MRI is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…16,22,23 A number of authors have suggested to identify PLC injury on CT scans, based on criteria such as facet diastasis, local kyphosis, and interspinous distance. 12,[24][25][26][27][28] The possibility to accurately identify PLC injury on CT scans would prove to be a great advantage, thus expediting treatment of TL fractures without MRI, especially in the clinical scenario of polytrauma with an unstable patient. 23 Although reports have suggested that CT-based radiological parameters may reliably detect PLC injury.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, many classify spine fractures utilizing general mechanical or morphological criteria, and using the CT scan as a tool for imaging-based diagnosis. [ 1 4 ] However, here, we utilized the MRI and the “gap” sign involving the ruptured LF to identify spinal fractures that were original missed.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, delayed evidence of instability may develop, and kyphosis (angle ≥10°), loss of vertebral height (≥50%), translation (X-rays >3.5 mm), and further fixed kyphosis can be found. [ 4 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is, however extremely useful in nerve root compression. It is also very useful in trauma [15]. There has been and equally encouraging advance in the so called 'percutaneous' techniques [16].…”
mentioning
confidence: 99%